Mapping historical landscapes in transformation an overview (2019)
In this postface overview of this edited volume, I have been asked firstly to highlight key themes; secondly to elaborate on them from my own experience of approaches to townscape and landscape research; and thirdly to identify areas that were not so prominent in these collected papers but deserve inclusion in a holistic overview of current research in these fields.